IranVeg – the Vegetation Database of Iran: current status and the way forward - Soghra Ramzi; Jalil Noroozi; Hamid Gholizadeh; Behnam Hamzeh’ee; Younes Asri; Amir Talebi; Halime Moradi; Parastoo Mahdavi; Seyedeh Saeedeh Tamjidi Eramsadati; Somayeh Zarezadeh; Asghar Kamrani; Omid Esmailzadeh; et al. (Vegetation Classification and Survey (VCS))
Iran, situated in Southwest Asia, showcases a diverse landscape, including three phytogeographical regions and two global biodiversity hotspots. This diversity is attributed to its intricate geology, mountainous terrain, wide altitudinal range, and heterogeneous climate, fostering a rich flora characterized by a significant proportion of endemism. We present an updated version of the Vegetation Database of Iran (IranVeg) (GIVD ID AS-IR-001), comprising 13,411 plots spanning six major habitat types. These encompass deciduous forests (18.0%), woodlands and shrublands (5.6%), steppes and other grasslands (52.0%), saline depressions (9.3%), wetlands (12.2%), and anthropogenic habitats (2.9%), derived from 100 published and unpublished resources, comprising 3,919 plant species, belonging to 961 genera and 147 families. The vegetation data of Iran have been assigned to 31 valid and invalid phytosociological classes. The oldest plots were recorded in 1936 in the Alborz Mountains in northern Iran, while more than 60% of all plots were collected after 2010. Plot sizes vary from less than 1 m2 to 10,000 m2 with the highest species richness of 101 species recorded in a 25 m2 montane grassland plot. IranVeg stands as the first national vegetation database in Iran, promising valuable insights into biodiversity patterns and facilitating the assessment of future environmental and anthropogenic changes. It remains open to further development through a collaborative network of vegetation scientists. This comprehensive database holds significant potential for advancing vegetation classification and survey efforts in Iran and beyond. Taxonomic reference: World Flora Online (WFO 2024).